Π-Plasmon absorption of carbon nanotubes for the selective and sensitive detection of Fe3+ ions. Issue 8 (4th May 2016) - Cheung, William; Patel, Mehulkumar; Ma, Yufeng; Chen, Yuan; Xie, Qiaoqiao; Lockard, Jenny V.; Gao, Yuan; He, Huixin
Abstract : The π-plasmon band of SWNTs can be used to selectively and sensitively detect Fe 3+ via the conjugation of Fe 3+ selective siderophores. Abstract : Inspired by the remarkable electronic and optical properties of single walled carbon nanotubes (SWNTs), various molecular sensing devices with sensitivity down to the single molecule level have been developed. However, most sensing approaches such as field effect transistors or near infrared (NIR) fluorescence require the rigorous debundling and separation of metallic tubes and semiconducting tubes in order to reach the desired high sensitivity. Interestingly, all carbon nanomaterials including carbon nanotubes, graphite, graphene, and even amorphous carbon exhibit extremely strong π-plasmon absorption in the ultraviolet region. This strong absorption has been studied as an undesired optical background for applications based on visible and NIR absorptions. For the first time, we found that the strong π-plasmon absorption of SWNTs in the ultraviolet region is extremely sensitive to ion binding. It is even much more sensitive than the absorption in the visible and NIR regions. Herein, we present our first exploration into using the extremely strong plasmon absorption of SWNTs to develop a new sensing platform for the detection of metallic ions. The detection selectivity is realized by modifying the surface of SWNTs with molecular ligands that have a high specificity for metal ions. As a demonstration, the new method is applied to selectively detect iron ions (Fe 3+ ) by modifying the surface of the SWNTs with deferoxamine (DFO), a natural bacterial siderophore, which has a high specificity and affinity for Fe 3+ . The selective detection of Fe 3+ in both aqueous solution and complex rain water is achieved with a pM level of sensitivity and detection limit. In situ resonant Raman spectroscopy demonstrated that the sensitive detection possibly involves electron transfer between the formed Fe–DFO complexes and the SWNTs. We envisage that it can be used to detect other metal ions when a specific binding chelator is attached to the carbon nanotube surface.